2017
DOI: 10.21608/esj.2018.8711
|View full text |Cite
|
Sign up to set email alerts
|

Microendoscopic bilateral Decompression via Unilateral Approach in Single and Multiple Level Lumbar Canal Stenosis: A Series of 583 Cases

Abstract: Background Data: Traditionally, lumbar canal stenosis (LCS) has been treated with conventional laminectomy involving wide resection of posterior supporting structures of the lumbar spine such as the supraspinous and inter-spinous ligamentum complex, the spinous process as well as wide areas of the lamina. In addition, this required a large incision of the skin and underlying musculoligamentous complex (posterior tension band). Purpose: The current study focuses on the clinical outcome and utility of minimally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 46 publications
(67 reference statements)
1
9
0
Order By: Relevance
“…26,42 However, this duration of hospital stay was less than that reported by Khoo and Fessler 14 (42 hours) and Lee et al 18 , whereas it was more than that presented by Rahman et al 26 (18 hours). The mean operating time per level was similar to that of Xu et al 41 , Pao et al 24 , and Wada et al 38 On the other hand, Khoo and Fesler 14 , Lee et al 18 , Kabil et al 12 22 , the mean operating time per level was 66.1 minutes (range, . The lower mean time might be attributed to the higher number of levels operated (753) and the more experience of the surgeon.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…26,42 However, this duration of hospital stay was less than that reported by Khoo and Fessler 14 (42 hours) and Lee et al 18 , whereas it was more than that presented by Rahman et al 26 (18 hours). The mean operating time per level was similar to that of Xu et al 41 , Pao et al 24 , and Wada et al 38 On the other hand, Khoo and Fesler 14 , Lee et al 18 , Kabil et al 12 22 , the mean operating time per level was 66.1 minutes (range, . The lower mean time might be attributed to the higher number of levels operated (753) and the more experience of the surgeon.…”
Section: Resultssupporting
confidence: 77%
“…Follow-up: Patients were followed up routinely at our outpatient clinic at 2 weeks, 3 months, 6 months, and 12 months. The mean follow-up was 10.5 ± 2.3 months (range, [6][7][8][9][10][11][12]. The assessment included clinical evaluation using NPRS and ODI.…”
Section: Postoperative Carementioning
confidence: 99%
“…A large retrospective study using micro-endoscopic decompression for management of 583 patients with lumbar canal stenosis, in which mean leg pain VAS improved from 8 preoperatively to 2 postoperatively. 4 In another study, 2 patients with degenerative lumbar canal stenosis have undergone bilateral decompression from unilateral approach, the VAS improved from 7±0.72 preoperatively to 2±0.72 postoperatively.…”
Section: Discussionmentioning
confidence: 92%
“…2,29,30,34,42 Only few series 35,37,41 have directly compared open laminotomy with open laminectomy. Several studies 1,2,20,22,31,33,38 have shown benefits of spinal endoscopic fenestration, including decreased blood loss, shorter operative time, shorter hospital duration, decreased postoperative narcotic requirement, decreased rate of infection and CSF leak, and a decrease in time required for returning to work.…”
Section: Discussionmentioning
confidence: 99%
“…Another shortcoming is the absence of a controlled group that would have suboptimal outcomes proven in the literature by several studies. 16,18,20,41 We did not like to offer our patients a procedure we believe would be suboptimal and not up to date. However, a 36-month follow-up that allowed observation of persistence of the initial good out-come and the prospective nature, the homogeneity of patient population, and the independent observers are strengths points of the current study.…”
Section: A a B Bmentioning
confidence: 99%